Profil Pelaksanaan Survei Lingkungan Belajar Jenjang PAUD di Povinsi NTB Tahun 2023 - Ardiansyah, Bakhtiar; Hikmawati, Latifah; Mufidah (Alpatih Harapan Semesta, 2024)
This research aims to obtain an overview of the profile of the implementation of sulingjar at the PAUD level in NTB Province in 2023, especially regarding the number of schools, principals, teachers and students who implement sulingjar as well as a description of implementation during sulingjar activities and the obstacles that occur. This type of research is survey research and documentation of data on the implementation of sulingjar at the PAUD level in NTB Province in 2023. The results of the research show that the number of schools implementing sulingjar PAUD in 2023 is 3,952 educational units out of 4,957 active educational units (79.73%). The participation of school principals was 3,860 out of 5,078 principals (76.01%). For teacher participation there were 11,280 people out of 14,698 teachers (76.75%) and for student participation there were 15,140 people out of 19,776 students (76.56%). Description of implementation during Sulingjar activities, on average, it was carried out smoothly and in accordance with technical instructions. In general, the obstacles that occur are signal interference and device limitations. Recommendations for various things that must be done by the city district education office are that it is necessary to increase the implementation of socialization and assistance for the implementation of sulingjar as well as the need to improve the facilities and infrastructure supporting activities.